EVALUASI PENERAPAN SISTEM PENGENDALIAN MANAJEMEN PADA PT INDO SARANA PRAKARSA - Joanne, Joanne; Hendi, Hendi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
During the accounting system transformation phase, PT Indo Sarana Prakarsa faced challenges in management control. To solve this problem, Community Service (PkM) activities focused on designing a management control system based on Standard Operating Procedures (SOP). This activity aims to improve internal communication, refine work procedures, and enhance the overall effectiveness and efficiency of the company's operations. The methods used in this activity are observation, interviews, and case studies. The results of implementing the management control system show that the new system helps the company improve workflow, enhance internal communication, and increase operational effectiveness. In addition, this system also plays a role in supporting regulatory compliance and providing an accurate basis for decision making. With effective implementation, this system is anticipated to have a substantial impact on the long-term growth, sustainability, and performance improvement of PT Indo Sarana Prakarsa.